PENGEMBANGAN BUKU CERITA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS I SDN KEDUNGREJO 1 KEREK KABUPATEN TUBAN - Novialita Angga Wiratama (Jurnal Tunas Pendidikan, 2023)
15 out of 22 pupils at SDN Kedungrejo 1 were found to be struggling with reading, according to the results of class teacher interviews and observations. Lack of practice is the cause of the challenge. This researcher wants to understand how storybook learning media are created and whether they are appropriate. The ADDIE model is used in R&D research. Materials expert validation sheets, media and language, teacher and student answer questionnaire sheets, and student test sheets were used as the data collection tools in this study. According to the findings of the validation test, using the results of the percentages of material experts (80%), media experts (90%) and linguists (93%), was extremely likely. Forms for teacher and student responses to questionnaires include useful learning criteria. 91% of questionnaires with responses from teachers and 89% of questionnaires with responses from students. Additionally, student test results reveal that the criteria for effective application are met with an 86% score for classical completeness. Student assessments and data from teacher and student response questionnaires demonstrate the viability, usefulness, and effectiveness of the designed storybook media